Answer:
f · g = 24x² - 52x + 24
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
Algebra I
Step-by-step explanation:
Step 1: Define
Identify
f(x) = 4x - 6
g(x) = 6x - 4
Step 2: Find f · g
(-2, 90 degrees) on apex
OB. 11 +78
O C. 6-12i
O D. 6+6i
Answer:
the correct answer is option B.
Step-by-step explanation:
First, we need to combine the terms inside the parentheses.
This gives us (8-3i)-(2-9i), or (8-3i)-(-2+9i).
We can then use the additive inverse property to simplify this to (8-3i)+2+9i, which is equal to (11+6i). Therefore, the correct answer is option B.
********************************
12y = 8
y =
given y ∝ x
To convert to an equation multiply by k the constant of variation
y = kx
to find k use the given condition y = 6 when x = 72
y = kx ⇒ k = = =
equation is → y = x
when x = 8 then
y = × 8 = =